Analysis of Mathematical Literacy Skills through PMRI Approaches of Elementary School Students - Wigati, Trinil; Wardono, Wardono; Purwanti, Eko (Universitas Negeri Semarang, 2020)
Students’ low mathematics literacy skills are due to the lack of students' skills to solve mathematical problems related to the real world. The objective of this study is to analyse the improvement of mathematics literacy skills of fifth-grade elementary school students and describe the mathematical literacy skills of elementary students through the PMRI approach. The method used was a mixed method with concurrent embedded design to analyse quantitative data on the quality of the PMRI approach and qualitative data to analyse the mathematical literacy skills of fifth-grade elementary school students. The results show that by using the PMRI approach, classical mastery learning can be achieved and the average students’ mathematical literacy skills are higher than the expository model. It is shown from the classical completeness results , it is 2.065> 0.4678. Therefore, the proportion of students who learn through the PMRI approach reaches more than 75%. While the data analysis of mathematics literacy skills of fifth-grade elementary school students has good ability in expressing mathematical ideas, turning problems into mathematical models, using strategies, symbols and tools correctly, and can make conclusions.